FOLKLOR CANDI CANGKUANG: DESTINASI WISATA BERBASIS BUDAYA, SEJARAH, DAN RELIGI - Sri Rustiyanti (Institute of Indonesia Arts and Culture (ISBI) Bandung, 2018)
ABSTRACT West Java has a variety of cultural, historical and religious potential that can be developed as the main tourist attraction, especially in Cangkuang Temple, Leles District, Garut Regency. Cangkuang Temple is one form of non-verbal folklore (artifact) inherited from two religions, namely Hinduism and Islam. The relics of Hinduism are the statue of Lord Shiva which is thought to date from the VIII century and the relics of Islam originated in the seventeenth century with the remains of the tomb of the Eyang Embah Dalem Arief Muhammad. The potential of Cangkuang Temple is quite interesting as one of the non-oil and gas foreign exchange tourism assets that needs to be improved in its management and empowerment. Therefore, the readiness of the Kampung Pulo community in developing tourism based on culture, history and religion still needs to be improved. Unpreparedness can be seen from the form of tourism development in each segment that has not been holistic and has not yet synergized with each other, regardless of the socio-cultural diversity of each, as well as the unclear market segments that will be targeted for development. Thus it is necessary to conduct research that aims to map the zoning of tourism development in accordance with the character of the community in the Garut Regency region. Analysis of the system of tourism-based development of culture, history, and religion that is suitable to be applied in the region also needs to be done in order to create an ideal model in tourism development and management in the Garut Regency region. The expected research results are the creation of an integrated tourism development model based on culture, history, and religion that can be applied in West Java, especially the Cangkuang Temple area. Keywords: Tourism Zoning, Cultural Tourism, Historical Tourism, Religious Tourism, Cangkuang Temple. ABSTRAK Jawa Barat memiliki beragam potensi budaya, sejarah, dan religi yang dapat dikembangkan sebagai daya tarik utama wisata, khususnya di Candi Cangkuang Kecamatan Leles, Kabupaten Garut. Candi Cangkuang adalah salah satu bentuk folklor bukan lisan (artefak) peninggalan dari dua agama, yaitu Hindu dan Islam. Peninggalan agama Hindu adalah patung Dewa Siwa yang diperkirakan berasal dari abad VIII dan peninggalan agama Islam berasal dari abad XVII dengan adanya peninggalan makam dari Eyang Embah Dalem Arief Muhammad. Potensi Candi Cangkuang cukup menarik menjadi salah satu asset wisata devisa non migas yang perlu ditingkatkan pengelolaan dan pemberdayaannya. Oleh karena itu, kesiapan masyarakat Kampung Pulo dalam pengembangan wisata berbasis budaya, sejarah, dan religi masih perlu ditingkatkan. Ketidaksiapan dapat terlihat dari bentuk pengembangan pariwisata masing-masing segmen yang belum holistik dan belum sinergi satu sama lain, tanpa memperhatikan keragaman socio-cultural masing-masing, serta adanya ketidakjelasan segmen pasar yang akan dijadikan sasaran pengembangannya. Dengan demikian perlu dilakukan penelitian yang bertujuan untuk memetakan zonasi pengembangan pariwisata yang sesuai dengan karakter masyarakat wilayah Kabupaten Garut. Analisis sistem pengembangan pariwisata berbasis budaya, sejarah, dan religi yang sesuai diterapkan di kawasan tersebut juga perlu dilakukan agar tercipta model yang ideal dalam pengembangan dan pengelolaan wisata di wilayah Kabupaten Garut. Hasil penelitian yang diharapkan adalah terciptanya sebuah model pengembangan pariwisata yang terpadu berbasis budaya, sejarah, dan religi yang dapat diterapkan di Jawa Barat, khususnya wilayah Candi Cangkuang. Kata Kunci: Zonasi Wisata, Wisata Budaya, Wisata Sejarah, Wisata Religi, Candi Cangkuang.